Physical, chemical, and microbiological characterization of Kettara Mine Tailings, Morocco - Benidire, Leila (2022)
The mining industry is of major importance to Morocco’s economy. However, the abandoned pyritic mines are a source of potentially toxic elements that can cause the disruption of the surrounding ecosystems, constituting a huge threat to wellbeing and human health. The present study aimed to analyze the physical and chemical characteristics of different types of tailings and to investigate the microbial populations of acidophilic bacteria involved in the oxidation of pyrite. Coarse and fine tailings collected from different zones of the mine (dike and pond) at two different depths (oxidized and non-oxidized residues) were analyzed for their pH, electrical conductivity, total organic carbon, total nitrogen, available P, major elements, and pseudo-total metal concentrations. The abundance of acidophilic bacteria was determined, and some acidophilic bacterial strains were isolated and tested for their metal tolerance. Tailings showed a pH ≈ 2, very low nutritional content, and high concentrations of Cu, As, Zn, and Pb, which were higher in the non-oxidized samples. The microbial counts of iron- and sulfur-oxidizing bacteria were higher than heterotrophic bacteria, with the highest numbers detected in the oxidized fine tailings. The five acidophilic bacteria isolated from the tailings were affiliated to genera Alicyclobacillus and Sulfobacillus, commonly found in this kind of environment.